P2_2 Hot Air in the House of Commons - Staab, Daniel; Watkinson, Emily Jane; Walach, Maria-Theresia; Rogerson, Zach (Physics Special Topics, 2012)
The power output associated with the heat flow from respiration of 650 MPs debating in the House of Commons was calculated. Heat flow directly into the air and from latent heat release during re-condensation of water vapour added to the exhaled breath was found to be 10.34 kW in total.